Operational Management for “Electric Vehicle Charging Station (eV-Station)” In Indonesia - Amin, Muzapar (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The charging station service business that will be carried out by the Company focuses on providing charging station services for electric vehicles. In addition to these main services, the Company has other services such as the provision of co-working space, Coffee Shop and also automatic car wash. The eV-Station business operational process requires asset costs and operational costs to run the company's operations. Although this business is relatively new, it has the potential to generate promising profits due to the popularity of electric vehicles today. The Company is committed to raising public awareness of the use of green energy in the hope that it can reduce the greenhouse effect and the effect of global warming at a wider level.